Symphony of the sorrow of love in two myths of love: Manijeh and Emojin (Analysis of two works with an approach to Jung's theory) - Sharifi Ghazijahani, Maryam; Novin, Hossein; Ghamari, Hossein; Salahi, Asgar (International Journal of Psychosocial Rehabilitation, 2021)
The story of Bijan and Manijeh composed by Ferdowsi (940-1020) and the Play of Cymbeline created by Shakespeare 1564-1616) are considered as famous love stories of world literature. The fame of these masterpieces and the similar content of them, despite the fact that the authors were from different era of history and characters’ same deeds and behaviour, are the reasons of choosing this topic for study. To examplify these similarities, we can refer to love and loyalty, patriarchy, and parents’ role in children’s important decision. The main theme of these literary works is love that does not recognize any limitation and defies the convention. The amorous heroes (Manijeh and Imogen) persist in getting married inspite of all difficulties. In the present article, first of all, the common contents and valuable messages of the authors are analyzed. Ferdowsi and Shakespear teach advisory points to their readers by creating amorous heroes in their masterpieces. Then, according to Jungian archetype, main characters of both valuable works, which included in the process of embracing love, are analyzed. In fact, By creating myths of love and the tortuous path of love, Ferdowsi and Shakespeare could induce anxiety or joy to the souls of readers in critical moments, which is a sign of the mastery and skill of the writers. In the present article, we conclude that the authors' positive view toward women and the continuation of love is of the sensible points of the stories.